Rearing of african catfish (clarias gariepinus) with high stocking density in bioflock techniques - Indah Dwi Lestari; Mulyadi '; Iskandar Putra (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This research was conducted from May until Juny 2013 at LaboratoryAquaculture of Technology University of Riau. The purpose of this research wasto investigate growth of the African catfish with high stocking density in bioflocktechniques. This research using exsperimental method and Completely RandomDesign (RAL) with three treatments and three replications, there are P1: stockingdensity of African catfish 100 fish/m2, P2: stocking density of African catfish 200fish/m2, dan P3: stocking density of African catfish 300 fish/m2. The result showedthat African catfish with high density in bioflock techniques was not effectedsignificantly on absolute growth weight, absolute growth length, daily growth rateand survival rate. But the best treatments in this research was stocking density offish 200 fish/m2, with high growth weight rate 17,25 g, lenght growth rate 7,84cm, daily growth rate 6,65%, and survival rate 94,66%.Keyword : African catfish, High density, Bioflock technology